DISTANCE LEARNING DURING THE PANDEMIC AT SDN BENCONGAN VI - Ramadhan; Sholeh Hidayat; Indhira Asih Vivi Yandari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The aim of this research was to provide an overview of the implementationof online distance learning during the pandemic at grade 4-C of elementary school. Learning before the pandemic was certainly different from learning during the pandemic since the SARS-CoV-2 virus was transmitted and caused Covid (Coronavirus Disease). Therefore, schools needed to adjust the learning implementation, such as changing the interactions and learning methods. The method used in this study was a qualitative descriptive method and the data collection techniques used in this study were interviews, observation, and documentation. The results of this study indicated that teachers carried out learning activities starting from preparing the Lesson Plan (RPP), learning media (videos), and learning resources such as textbooks and Student Worksheets (LKS). During the implementation of online distance learning, the teacher carried out preliminary activities such as praying, asking students' readiness, and apperception, then, continuing to the core activities in which the teacher delivered the material by using standard language, the learning resources, and doing question and answer with students. Then, during the assessment, the teacher assessed students' spiritual and social attitudes through learning via Google Meet, assessed students’ knowledge using Google Forms, and conducted skills assessments in the form of product assessments and practice assessments.